Development of microglia in fetal and postnatal neocortex of the pig, the European wild boar (Sus scrofa). Issue 9 (14th December 2021) - Sobierajski, Eric; Lauer, German; Aktas, Meriyem; Beemelmans, Christa; Beemelmans, Christoph; Meyer, Gundela; Wahle, Petra
Abstract: Knowledge on cortical development is based mainly on rodents besides primates and carnivores, all being altricial. Here, we analyzed a precocial animal, the pig, looking at dorsoparietal cortex from E45 to P90. At E45, most ionized calcium‐binding adapter molecule 1‐positive (Iba1+) cells had a macrophage‐like morphology and resided in meninges and choroid plexus. Only a few cells were scattered in the ventricular and subventricular zone (VZ and SVZ). At E60/E70, all laminar compartments displayed microglia cells at a low‐to‐moderate density, being highest in VZ and SVZ followed by intermediate zone/white matter (IZ/WM). The cortical plate and marginal zone displayed only a few Iba1+ cells. Cells were intensely labeled, but still had poorly arborized somata and many resembled ameboid, macrophage‐like microglia. Concurrent with a massive increase in cortical volume, microglia cell density increased until E85, and further until E100/E110 (birth at E114) to densities that resemble those seen postnatally. A fraction of microglia colabeled with Ki67 suggesting proliferation in all laminar compartments. Cell‐to‐cell distance decreased substantially during this time, and the fraction of microglia to all nuclei and to neurons increases in the laminar compartments. Eventually, of all cortical DAPI+ nuclei 7–12% were Iba1+ microglia. From E70 onwards, more and more cells with ramified processes were present in MZ down to IZ/WM, showing, for instance, a close association with NeuN+, NPY+, and GAD65/67+ somata and axon initial segments. These results suggested that the development of microglia cell density and morphology proceeds rapidly from mid‐gestation onwards reaching near‐adult status already before birth. Abstract : The picture illustrates a boar fetus 2 weeks before birth and its highly gyrated brain. A representative coronal section through one hemisphere indicates regions of interest for assessing, in the laminar compartments, the changes in morphology and cell density. Microglia cells reach adult‐like cell density and morphology well before birth. Cells interact with neuronal somata and axon initial segments by late midgestation. Depending on the laminar compartment, microglia cells represent 7–12% of all cortical cells.